If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -28 = -6(7 + -1x) Reorder the terms: -28 + 8x = -6(7 + -1x) -28 + 8x = (7 * -6 + -1x * -6) -28 + 8x = (-42 + 6x) Solving -28 + 8x = -42 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -28 + 8x + -6x = -42 + 6x + -6x Combine like terms: 8x + -6x = 2x -28 + 2x = -42 + 6x + -6x Combine like terms: 6x + -6x = 0 -28 + 2x = -42 + 0 -28 + 2x = -42 Add '28' to each side of the equation. -28 + 28 + 2x = -42 + 28 Combine like terms: -28 + 28 = 0 0 + 2x = -42 + 28 2x = -42 + 28 Combine like terms: -42 + 28 = -14 2x = -14 Divide each side by '2'. x = -7 Simplifying x = -7
| 3y-36=2y | | -28=7n | | 3/16.8 | | 2m=6m-20 | | -61=-48+c | | -.25x+3.5=-.625 | | -2(5+2r)=-6-5r | | 1/3x-3=-2 | | (3-z)(3z+4)=0 | | 81x^2-27x-18=0 | | 94=t+6 | | T^3-12t^2+45t+2=0 | | 6y+7/5 | | 4x+6y=-30 | | 5(b+1)=2(b-5) | | 5u(u-8)(u-6)=0 | | 5a-8whena=9 | | 5b+5=2b-10 | | 3x+15=57 | | y-79=-61 | | -(1+5n)=-4n | | 2x+4y=122 | | 73-6x=3x+23 | | 2x+19=-79-9x | | 2x+19=-19-9x | | -57+r=66 | | 63+w=92 | | -3pie+w=2pie | | 9-8x=30-22x | | -20-5x=5-10 | | 22=46+b | | 64+48v+9v^2=0 |